Using general practice data to monitor influenza vaccination coverage in the medically at risk: a data linkage study. Issue 9 (17th September 2019) - Badmus, Dauda; Menzies, Robert
Abstract : Objective: To examine the possibility of using data from a network of Australian General Practices (GPs) to estimate influenza vaccination coverage in Australians medically at risk. Design: Data electronically extracted from a large national network of Australian GP clinics (MedicineInsight) was analysed for annual influenza vaccination coverage from 2008 to 2014. We compared the results with the 2009 and 2014 Adult Vaccination Survey. We adjusted for differences in the distribution of age, risk groups and provider types. Setting: All states in Australia. Participants: GPs participating in MedicineInsight programme. Interventions: Not applicable. Main outcome measures: Annual vaccination coverage across risk groups as recorded in Adult Vaccination Survey in 2009 and 2014 were compared with vaccination coverage in MedicineInsight. The impact of National Immunisation Programme expansion of free vaccine in 2010 to cover patients aged <65 years with medical risk factors. Results: The proportion of MedicineInsight patients aged ≥18 years and diagnosed with medical risk factors was higher in 2014 (33.2%), compared with the AVS in 2009 (25%). In 2009, influenza vaccination coverage estimates for those aged 18–64 years with medical risk factors was lower for MedicineInsight patients compared with the AVS (26% vs 36%). There was no evidence of any change in coverage between 2008 and 2014, despite the vaccine being available free of charge to this group from 2010. Conclusion: General practice databases have the potential to help fill the gap in vaccination coverage data in patients with medical risk factors.